2020
DOI: 10.12659/msm.923025
|View full text |Cite|
|
Sign up to set email alerts
|

Wnt-C59 Attenuates Pressure Overload-Induced Cardiac Hypertrophy via Interruption of Wnt Pathway

Abstract: Departmental sources Background: Cardiac hypertrophy usually results in heart failure and is an important cause of mortality worldwide. Wnt/bcatenin signaling pathway hyper-activation is involved in the pathogenesis and progression of cardiac hypertrophy. Wnt-C59 is a small molecular compound, which strongly and specifically targets at Porcupine to pharmacologically inhibit Wnt palmitoylation, secretion, and other biological activities. However, the role of Wnt-C59 in cardiac hypertrophy remains unknown. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…It has been shown to suppress the proliferation of intestinal stem cells and inhibit tumour growth 25 26. A recent study has reported that WNT-C59 attenuates pressure overload-induced cardiac hypertrophy 27. In this study, WNT-C59 significantly ameliorated both in vivo and in vitro DCM phenotypes, thus suggesting immediate translational potential.…”
Section: Discussionsupporting
confidence: 57%
“…It has been shown to suppress the proliferation of intestinal stem cells and inhibit tumour growth 25 26. A recent study has reported that WNT-C59 attenuates pressure overload-induced cardiac hypertrophy 27. In this study, WNT-C59 significantly ameliorated both in vivo and in vitro DCM phenotypes, thus suggesting immediate translational potential.…”
Section: Discussionsupporting
confidence: 57%
“…Conversely, inhibitors of Wnt signalling limit fibrosis. For example, Wnt-C59, which inhibits porcupine to block Wnt secretion, attenuates renal and cardiac fibrosis [ 24 , 25 ]. Small-molecule inhibitors of FZD8 have been shown to inhibit ECM gene expression [ 26–28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of the Wnt signaling pathway in CRA-induced VI has not yet been reported, studies have shown that β-catenin-mediated Wnt signaling plays a critical role in cardiac hypertrophy [ 61 ], vascular calcification [ 62 ], arterial stiffness [ 63 ], and angiogenesis [ 64 ]. We have determined the expression of 5 indicators related to the Wnt signaling pathway; however, the mechanism underlying the involvement of the Wnt signaling pathway in CRA-induced VI remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%